(untitled) (Contemporary Mathematics, 2025)
In this paper, we state the value of edge irregularity strength for the complete graphs Kn of order n ≥ 3, wheel graphs Wn where n ≥ 3 and the union of disjoint graphs. Also we state a lower bound for edge irregularity strength for the complete sun graph of order 2n and size .